304 Stainless Steel Corrosion Rate in HNO3 Solution - Hendrikus Dwijayanto Wibowo Sutarjo (Trigin Publisher, 2021)
This research purpose to find out the corrosion rate of Stainless Steel 304 in sulfuric acid. Immerse process do in 700 C temperature for 6 hours and than in 290C temperature for 18 hours every day. This condition aim to get closer to the actual use in the manufacture of tubes of reactor SAMOP (Sub Critical Assembly for Mo99 Prad Action). Specimen atfer TIG welding and electric arc welding cleaned from crust and than measured, drawing balanced, and record the first weight. And than specimen innerse to sulfuric acid pH 0.2 and 0.5 in 700C temperature for 6 hours and than in 290C temperature for 18 hours every day for 3 month. Weight recording has been done every week. The survey findings show heavy shrinkage sample, it is well visible on the corrosion pH 0.5 in electric arc welding of 0.105 gram/dm2/month for corrosion 0.026 gram/dm2/month without welding and pH 0.2, arc welding of 0.045 gram/dm2/ month, pH 0.2 no Las 0.02 gram/dm2/month. Specimens that have been welded have significant differences in corrosion rate compare to specimens that have not welded.